Knowledge, attitude and practice towards pharmacovigilance among postgraduate medical students at a tertiary care hospital: a cross sectional questionnaire based study - K., Vishnu; K. R., Mamatha; C. R., Jayanthi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reaction (ADR) is major global health problem affecting both children and adults. ADRs are among the leading cause of mortality and morbidity leading to prolonged hospitalization. Hence, spontaneous reporting of ADRs by healthcare professionals forms the backbone of pharmacovigilance. Therefore, there is an urgent need for sensitization about drug safety monitoring among healthcare professionals (HCPs). Methods: A cross sectional questionnaire based study was conducted among 200 postgraduate medical students between April 2016 and May 2016 using a pre-validated questionnaire. Descriptive statistics was used for analysis. Results: Among 200 questionnaires distributed, only 150 provided responses reflecting a response rate of 75%. The postgraduates who understood the definition of adverse drug reaction and pharmacovigilance were 90% and 64% respectively. The most encouraging finding was 97% of postgraduates thought that reporting an ADR was necessary which in turn increases the patient safety. 60% postgraduates were unaware that the nurses and pharmacists also had the responsibility of reporting ADR. The postgraduates who encountered ADRs during clinical practice were 79% whereas reporting was only 2%. Conclusions: This study suggests that even though majority of postgraduates have better knowledge and attitude towards pharmacovigilance and ADR, the practice of reporting ADRs is inadequate. Therefore, there is an urgent need for educational intervention in the form of training programmes and continued medical education (CME) periodically to encourage ADR reporting among the postgraduates.